La migración por el feriado bancario y su influencia en el desarrollo social de la parroquia de Guasuntos cantón Alausí - Tamay Nugshi, Segundo Manuel (2018)
Human mobility is a social problem that has increased more frequently in recent years, mainly that caused by socio-economic conditions, the lack of employment opportunities arise social groups that migrate to places of greater economic development with the hope to look for a better future. In the years that have elapsed, the Ecuadorian migration has been due to the strong inequalities in terms of development and power between social classes, the migratory waves, originating in the underdeveloped countries in relation to the developed countries, in the same way in the Guasuntos parish Alausí town, emigration has become present within this social group. The economic crisis experienced in Ecuador, the banking holiday marked the life of all Ecuadorians, especially the working class, on March 8, 1999, the government of Jamil Mahuad´s government took the step of freezing savers accounts for one year, and as one of the consequences of this measure was migration. This huge wave of migration had positive and negative influences, apart from the sad departure of many family members who were looking for better job opportunities. As a consequence of the migratory wave according to the interviews, the economic reactivation takes place in the Guasuntos parish, canton Alausí.